2017
DOI: 10.3390/ijms18040852
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Protects PC12 Cells from Tunicamycin-Mediated Cell Death via Reactive Oxygen Species Scavenging and Modulation of Nrf2-Driven Gene Expression, SIRT1 and MAPK Signaling in PC12 Cells

Abstract: Background: Fisetin (3,7,3′,4′-tetrahydroxyflavone) is a dietary flavonol and exhibits antioxidant, anti-inflammatory, and neuroprotective activities. However, high concentration of fisetin is reported to produce reactive oxygen species (ROS), induce endoplasmic reticulum (ER) stress and cause cytotoxicity in cancer cells. The aim of this study is to investigate the cytoprotective effects of low concentration of fisetin against tunicamycin (Tm)-mediated cytotoxicity in neuronal-like catecholaminergic PC12 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…A previous study has shown that FST promoted autophagic degradation of phosphorylated tau via the activation of TFEB and Nrf2 transcription factors (Kim et al, 2016), suggesting that FST exerts pro-autophagy effects. However, another study has also shown that FST exerts autophagy repressing effects (Yen et al, 2017) at doses < 20 µM in tunicamycin-mediated cells. This observation appears contrary to our conclusions, yet consistent with data from Figures 3 and 4, where we show that FST (5 mM) decreased L-02 cell viability, inhibited autophagy and upregulated inflammasome associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that FST promoted autophagic degradation of phosphorylated tau via the activation of TFEB and Nrf2 transcription factors (Kim et al, 2016), suggesting that FST exerts pro-autophagy effects. However, another study has also shown that FST exerts autophagy repressing effects (Yen et al, 2017) at doses < 20 µM in tunicamycin-mediated cells. This observation appears contrary to our conclusions, yet consistent with data from Figures 3 and 4, where we show that FST (5 mM) decreased L-02 cell viability, inhibited autophagy and upregulated inflammasome associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Tunicamycin, a pharmacological ER stress inducer, can stimulate tumor cell apoptosis [ 17 , 18 ]. Therefore, it has been used to develop an anti-cancer drug [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported to decrease the levels of isoflurane-induced cytosolic calcium and reactive oxygen species [ 121 ]. Likewise, cellular ROS production induced by several oxidative damaging agents was attenuated by pretreatment with chrysin (2) [ 122 ], naringenin (3) [ 123 ], astilbin (4) [ 53 ], icariin (5) [ 124 ], 7,8-dihydroxyflavone (6) [ 125 ], hyperoside (7) [ 126 ], baicalein (8) [ 127 ], rutin (11) [ 128 ], luteolin (12) [ 129 ], fisetin (15) [ 130 ], nobiletin (16) [ 131 ], kaempferitrin (10) [ 132 ], and quercetin (17) [ 133 ].…”
Section: Resultsmentioning
confidence: 99%